ANALISIS PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP TINGKAT KEPUASAN KONSUMEN (Studi KasusFood Court UNY) - Anita Mustikasari (Jurnal Ilmiah Dinamika Teknik, 2020)
The high business competition in the culinary field is certainly a challenge for business people to retain their customers. Product quality and service quality are important to attract consumers. Therefore, there are many ways undertaken by business owners to meet consumer expectations by creating a satisfaction. This study aims to determine the relationship between product quality and service quality on consumer satisfaction at UNY Food Court using Multiple Linear Regression analysis with SPSS 16.0 software. From the results it was found that there was a significant influence between the Product Quality (X1) and Service Quality (X2) variables to the Consumer Satisfaction variable (Y) with the level (Sig 0,000). The contribution of Product Quality (X1) and Service Quality (X2) variables to the Consumer Satisfaction (Y) variable at UNY or R square Food Court is 67.4%. So it can be concluded that the Food Court must always evaluate, improve and also innovate the level of service and product in order to increase consumer satisfaction which has an impact on increasing revenue. Keywords: Product quality, Service quality, Consumer satisfaction